2021
DOI: 10.3390/en14185787
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Consumption in Consumer Behavior in the Time of COVID-19: Topic Modeling on Twitter Data Using LDA

Abstract: By using text mining techniques, this study identifies the topics of sustainable consumption that are important during the COVID-19 pandemic. An Application Programming Interface (API) streaming method was used to extract the data from Twitter. A total of 14,591 tweets were collected using Twitter streaming API. However, after data cleaning, 13,635 tweets were considered for analysis. The objectives of the study are to identify (1) the topics users tweet about sustainable consumption and (2) to detect the emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 131 publications
0
15
0
Order By: Relevance
“… Lahath et al (2021) ; Liu et al (2021) Sustainability Awareness Higher awareness of the environmental consequences of food waste Higher awareness of the ethics of food waste. High sustainability awareness Leads to responsible behaviour Less food wastage Burlea-Schiopoiu et al (2021) , Pappalardo et al (2020) , Pires et al (2021) , Vittuari et al (2021) , Brzustewicz and Singh (2021) More Dieting More time to take diet. Diet leads to a planned meals routine.…”
Section: Thematic Analysismentioning
confidence: 99%
“… Lahath et al (2021) ; Liu et al (2021) Sustainability Awareness Higher awareness of the environmental consequences of food waste Higher awareness of the ethics of food waste. High sustainability awareness Leads to responsible behaviour Less food wastage Burlea-Schiopoiu et al (2021) , Pappalardo et al (2020) , Pires et al (2021) , Vittuari et al (2021) , Brzustewicz and Singh (2021) More Dieting More time to take diet. Diet leads to a planned meals routine.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Customers can place orders without going to the store to compare goods, which greatly improves efficiency [3]. Western research on consumer behavior originated from "consumer analysis" [4]. However, most consumer behavior patterns are driven by experience or theory [5].…”
Section: Introductionmentioning
confidence: 99%
“…The topic coherence metric represents the degree of semantic similarity for different topics (Stevens et al, 2012). The perplexity metric measures the performance of a model based on the learned set of topics (Brzustewicz and Singh, 2021). An analysis of topic coherence and perplexity conducted for the number of topics ranging from 0 to 20 revealed 10 as a satisfactory number of topics in this study because this number showed the highest levels of topic coherence and lowest levels of perplexity (Tang et al, 2019).…”
Section: Topic Modeling Analysismentioning
confidence: 99%